Innovative Teaching Practices: Leveraging Canvas Learning Management System in Alfa Centauri Senior High School - Maulana Mulyawandi, Arli; Widia Astuti, Renny; Luthfiyanti, Witri (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to provide insight for educators and innovation for administrators within their teaching practices, also improve educational outcomes through technology. Due to the need for distance learning, Alfa Centauri Senior High School has enhanced the learning experience through Canvas LMS as a powerful teaching and learning tool. This paper explores the innovative teaching practices facilitated by the implementation of Canvas LMS at Alfa Centauri Senior High School. The impact of Canvas on both teachers and students is assessed through qualitative analysis, highlighting best practices, challenges faced during implementation, and strategies for effective use. The findings illustrate that leveraging Canvas not only streamlines the administrative tasks but also fosters a more interactive and supportive learning environment. In conclusion, Canvas LMS is at its best in terms of practicality for both teachers and students at SMA Alfa Centauri.